2018
DOI: 10.1242/dmm.035311
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Fgfr2c causes craniofacial bone hypoplasia and ameliorates craniosynostosis in the Crouzon mouse

Abstract: FGFR2c regulates many aspects of craniofacial and skeletal development. Mutations in the FGFR2 gene are causative of multiple forms of syndromic craniosynostosis, including Crouzon syndrome. Paradoxically, mouse studies have shown that the activation (Fgfr2cC342Y; a mouse model for human Crouzon syndrome), as well as the removal (Fgfr2cnull), of the FGFR2c isoform can drive suture abolishment. This study aims to address the downstream effects of pathogenic FGFR2c signalling by studying the effects of Fgfr2c ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 46 publications
(70 reference statements)
1
13
0
Order By: Relevance
“…FGFR activation of pERK1/2 is important for several stages of osteoblastogenesis, including osteoprogenitor proliferation, and in the induction and stabilization of RUNX2 ( Choi et al, 2008 ; Yoon et al, 2014 ). Augmentation of pERK1/2 signaling either through overactivation of FGFRs , downregulation of its inhibitors, or downregulation of ERF that regulates the export of pERK from the nucleus, all result in craniosynostosis ( Lee et al, 2018a ; Lee et al, 2018b ; Timberlake et al, 2017 ; Twigg et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…FGFR activation of pERK1/2 is important for several stages of osteoblastogenesis, including osteoprogenitor proliferation, and in the induction and stabilization of RUNX2 ( Choi et al, 2008 ; Yoon et al, 2014 ). Augmentation of pERK1/2 signaling either through overactivation of FGFRs , downregulation of its inhibitors, or downregulation of ERF that regulates the export of pERK from the nucleus, all result in craniosynostosis ( Lee et al, 2018a ; Lee et al, 2018b ; Timberlake et al, 2017 ; Twigg et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…FGFR2 is a highly conserved receptor tyrosine kinase (RTK; Lee et al 2018) upstream of several signal transduction pathways that are crucial for osteogenic differentiation (Miraoui et al 2009). Several SNPs in FGFR2, in particular rs2162540 and rs11200014, have been identified as susceptibility variants for skeletal malocclusion (da Fontoura et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Studies utilizing genetic mouse models of syndromic craniosynostosis have shown that the pathogenesis can include pre-ossification development defects, such as insufficient differentiation of migrating cranial neural crest cells into mesenchymal cells, deficient neural crest cell renewal, and inappropriate mesoderm and/or neural crest cell localization to sites of bone and suture formation [ 10 , 84 , 85 ]. Craniosynostosis pathogenesis can also include post-ossification defects in cranial bone/suture boundary maintenance, premature cranial progenitor cell lineage commitment and suture osteogenesis, diminished proliferation, and/or apoptosis of suture stem or cranial bone progenitor cells [ 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 ]. Mechanisms differ, depending upon the genetic abnormality and involved suture.…”
Section: Cranial Neural Crest Cells In the Pathogenesis Of Craniofmentioning
confidence: 99%
“…Unlike Pfeiffer and Apert syndromes, there are no limb or digit abnormalities in individuals with Crouzon syndrome, suggesting that the mutation has greater specificity of effects on neural crest-derived craniofacial tissues. Indeed, lineage-restricted over-expression of Fgfr2c in neural crest-derived tissues causes midface hypoplasia and cleft palate, whereas lineage-restricted over-expression in mesoderm-derived tissues yields no craniofacial phenotype [ 86 ]. The Fgfr2 C342Y/+ mouse model phenocopies the craniofacial abnormalities seen in individuals with Crouzon syndrome, including the hallmark features of coronal and facial suture fusion, midface hypoplasia, hypertelorism and ocular proptosis [ 87 , 130 ].…”
Section: Mechanisms Underlying Coronal Craniosynostosismentioning
confidence: 99%